The construction of Boullèe’s abstract portrait through the images of Peter Greenaway’s film The Belly of an Architect - Solís Rebolledo, Gabriela; Solís Rebolledo, Patricia (Eikón / Imago, 2025)
The present research analyzes the image of a frame from Peter Greenaway’s film The Belly of an Architect in light of his interpretation of Étienne-Louis Boullée, focusing attention on the inherent complexity of artistic creation and the idea of the figure of the architect. Among the various possible levels of reading, this research addresses the aspects of allegory and personification of the concepts that represent Boulléan architecture through the main character, Stourley Kracklite, considering that he sees himself as Boullée’s heir, due to which he appropriates the thought, drawings and projects of this architect. The analysis makes visible Greenaway’s aesthetic notion regarding the abstract portrait of Boullée represented through the conceptual relationship between the Boullean project of the Cénotaphe à Newton, the treatise Architecture. Essai sur l’Art, the monuments of Antiquity and Italian Renaissance painting, taken up in the film frame to establish Boullée’s identity and offer a perspective on his architecture and its sources.